Evaluation Lessons from a Theatre Company - Tamara M. Walser; Keith Bridges; Kate Mattingly (The Evaluation Center at Western Michigan University, 2008)
Charter Theatre is a small professional theatre in Washington, DC. Its mission is to develop and produce new plays. This includes seeking out new plays, working with the playwrights to clarify their aesthetic intentions, developing a strong script, and then producing those plays. Like other organizations, Charter Theatre wants to be accountable. Its members believe they are responsible to the audience to do the best work they can do. They saw the need for evaluation early on-a repeatable process to assure the quality of their work. However, they didn't want a factory that would create the same kind of work over and over. In theatre, variety is part of the point. In developing their process, Charter Theatre's Artistic Director questioned," How do you evaluate a play without sucking all the life from it?"